Influência dos fatores climáticos sobre a periodicidade de crescimento vegetativo do café (Coffea arabica L) - Santos Barros, Raimundo; Maestri , Moacyr (Revista Ceres, 2025)
Influence of Climatic Factors on Growth Periodicity of Coffee (Coffea arabica L.). Weekly measurements of vegetative growth carried out on coffee(Coffea arabica L.) in Viçosa (200 45’S, 420 15’W, elevation 650 m), Minas Gerais, Brasil, in September 1970 through August 1971,showed that the main trunk, lateral branches and leaves had a similar growth periodicity. Irrigated and nonirrigated plants behaved similarly.